Pengenalan Dan Pengaplikasian Microsoft Word Dan Microsoft Excel Di SD Dan SMP Satu Atap Doromena Distrik Depapre Kabupaten Jayapura - Joe M. W. W. Kafiar; Magdalena Nabyal; Kaleb Beka Tabuni; Obias Kogoya; Esty Zulfahnur; Septiani Anastasya; Rani Tikupadang; Alisya Arifia Destiavin; Lidia Depondoye; Novelien Angel Pekey; Kezia Anou (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2024)
Mastery of information technology and Communication (ICT) is a necessity in facing the era of globalization. One of the applications in computers widely used for manufacturing assignments at school are Microsoft Word and Microsoft Excel. This service activity is carried out with the aim of to provide assistance to learners at Doromena Inner One-Stop Elementary and Junior High School to apply Microsoft Word and Microsoft Excel. The training was conducted four times, namely on August 10, 11, 14, and 15, 2023 at Doromena One-Roof Elementary and Junior High School, Jayapura Regency, Papua Province, which focused on grade 5 elementary and grade 8 junior high school students. The training provided covers the reasons for the importance of computer mastery, the theoretical basis of Microsoft Word and Excel, and their application. The methods used are lectures, practices, and questions and answers. To determine the success of the activity program that has been implemented, an evaluation is carried out by providing a practical exam to determine the level of understanding of students related to the material and training that has been given.